The Effect of Ultrafast Heating in Cold-Rolled Low Carbon Steel: Recrystallization and Texture Evolution - Monsalve-Gonzalez, A; Castro-Cerda, F (Multidisciplinary Digital Publishing Institute (MDPI), 2016)
The microstructure and texture evolution of cold-rolled low carbon steel after ultrafast heating and quenching is investigated. Experiments were carried out at heating rates of 150 °C/s and 1500 °C/s. The recrystallization of ferrite is studied by scanning electron microscopy and electron backscattered diffraction techniques. The texture evolution of cold rolled steel during ultrafast heating was studied, making it possible to estimate the precise effect of heating rate on the orientations of newly formed grains. The experimental results showed that the recrystallization of ferrite was not completed before the full transformation of austenite. The noticeable increase in the fraction of recrystallized grains of diameter less than 1 µm, when the heating rate is increased from 150 °C/s to 1500 °C/s suggests that the increase of the heating rate enhances the nucleation of ferrite. The crystallographic orientations in recrystallized ferrite are strongly influenced by the heating rates. The effect of heating rate in the releasing of stored energy, carbon diffusion and spheroidization of cementite might explain some differences in textures observed in recrystallized ferrite. © 2016 by the authors; licensee MDPI, Basel, Switzerland.